A Clinical Study to Re-Evaluate the Efficacy of Vidari Churna on Krusha - Kailas Patil, Amol (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This paper presents an overview of a clinical study to re-evaluate the efficacy of vidari churna on krusha.
Keywords: clinical study; reevaluate; efficacy; vidari; churna; krusha